Prevalência da alexitimia na anorexia nervosa e sua associação com variáveis clínicas e sociodemográficas = Prevalence of alexithymia in anorexia nervosa and its association with clinical and sociodemographic variables - Sandra Torres (2011)
Objective: To analyze the prevalence of alexithymia in anorexia nervosa and its relationship with clinical and sociodemographic variables, such as, body mass index, anorexia nervosa duration, age, years of education and socioeconomic status. Methods: Two groups of female participants, between the ages of 13 and 34 years, were recruited. One group was composed of 80 participants with anorexia nervosa (AN Group) and the other consisted of 80 healthy participants (Control Group). The Portuguese version of the Toronto Alexithymia Scale - 20 items - was applied to both groups. Results: The prevalence of alexithymia in the AN Group was 62.5% and 12.5% in the Control Group. The mean values of alexithymia (total score and factors) did not significantly differ between the two AN subtypes, and both subtypes presented higher statistical values when compared to the Control Group. Alexithymia did not correlate with clinical and sociodemo graphic variables, with the exception of years of education, which had a positive and low association with alexithymia. Conclusion: Patients with anorexia nervosa revealed a high prevalence of affect regulation deficits regardless of their weight, duration of the disease, age and socioeconomic status. Therapy should focus on a systematic intervention in the domain of emotional regulation.